2003
DOI: 10.1590/s0104-42302003000300035
|View full text |Cite
|
Sign up to set email alerts
|

Influência do tratamento neoadjuvante na morbi-mortalidade das esofagectomias

Abstract: RESUMO -OBJETIVOS. Avaliar a influência do tratamento neoadjuvante (quimioterápico e/ou radioterápico) nas complicações pós-operatóriasO tratamento do câncer de esôfago esbarra em dificuldades impostas pelo próprio tumor, estado geral do paciente e opções terapêuticas agressivas. A cirurgia persiste como tratamento principal, podendo atingir níveis de cura expressivos nos estágios iniciais da doença. A radioterapia e quimioterapia têm sido utilizadas como associadas à cirurgia na tentativa de melhorar os resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(31 reference statements)
1
1
0
4
Order By: Relevance
“…Some authors have indicated that studies based on retrospective hospital-based cohorts have signifi cant limitations with regard to correlating these smokingrelated clinical conditions with certain outcomes, as concluded by Tho et al 19 Even though the comorbidity frequency data from the present study did not allow any correlation between the presence of these conditions and greater use of healthcare resources, a considerable proportion of the patients presented comorbidities associated with the diagnosis of cancer, notably heart and lung diseases. Our fi ndings corroborate those of Janssen-Heinjen et al, 10 who investigated the prevalence of comorbidities associated with lung cancer in the Netherlands, and those of Tomasich et al 20 regarding esophageal cancer in Brazil. Other limitations of the present study need to be pointed out.…”
Section: Discussionsupporting
confidence: 91%
“…Some authors have indicated that studies based on retrospective hospital-based cohorts have signifi cant limitations with regard to correlating these smokingrelated clinical conditions with certain outcomes, as concluded by Tho et al 19 Even though the comorbidity frequency data from the present study did not allow any correlation between the presence of these conditions and greater use of healthcare resources, a considerable proportion of the patients presented comorbidities associated with the diagnosis of cancer, notably heart and lung diseases. Our fi ndings corroborate those of Janssen-Heinjen et al, 10 who investigated the prevalence of comorbidities associated with lung cancer in the Netherlands, and those of Tomasich et al 20 regarding esophageal cancer in Brazil. Other limitations of the present study need to be pointed out.…”
Section: Discussionsupporting
confidence: 91%
“…Pelos dados disponíveis na plataforma SIH/DATASUS, não é possível determinar o tipo de técnica cirúrgica utilizado em cada procedimento. Sabe-se, porém, que dentre as duas categorias mais utilizadas para a realização da esofagectomia (anastomose torácica e anastomose cervical), a anastomose cervical possui maior morbimortalidade, devido a maior incidência de fístulas 8 , com elevada letalidade hospitalar relacionada a esta complicação. Além disso, as limitações das pesquisas baseadas em dados obtidos pela plataforma do DATASUS são conhecidas.…”
Section: Discussionunclassified
“…Alguns trabalhos avaliando o tratamento neo-adjuvante foram publicados com resultados controversos especialmente em relação à possível melhora da sobrevida as custas de maiores complicações peri-operatórias 1,2,4,8,11,14,15,16,17,18,19,21,22,28,35,36,38,40 .…”
Section: Discussionunclassified
“…Tomasich et al 36 relatam também complicações pleuropulmonares elevadas nos doentes operados e submetidos ao tratamento neoadjuvante e mortalidade hospitalar de 13,7%.…”
Section: Discussionunclassified